Spectrum of Multimodality Findings in Post-surgical Breast Cancer Imaging - Ramli Hamid, Marlina T.; Rahmat, Kartini; Hamid, Shamsiah Abdul; Kirat Singh, Shaleen Kaur; Hooi, Tan Gie (Current Medical Imaging, 2019)
Background: Breast cancer is the commonest cancer affecting Malaysian women, accounting for an estimated 30% of all new cancer diagnosed annually. Improvements in breast cancer management have increased the breast cancer survival rate in Malaysia. Clinical and radiological surveillance of the treated breast is vital, as early detection of recurrence improves patient’s survival rate. Discussion: As surgery and radiotherapy alter the appearance of the breasts, distinguishing between recurrence and benign post-surgical changes can be challenging radiologically due to overlapping features. Despite this, differentiation between these two entities is usually possible by recognizing characteristic features of post-treatment sequelae and the evolution of the appearance of the conservatively treated breast by comparing interval findings on serial studies. Conclusion: This pictorial review aims to describe the typical and unusual features of post-treated breasts in the multimodality imaging workup of an established breast care centre in a teaching hospital in Malaysia.
Keywords: recurrence